Profile of a writer academician: an annotated bibliography of Shaharom TM Sulaiman's work / Azmi Ab Rahman, Mohd Nizam Yunus and Yamin Kamis - Ab Rahman, Azmi; Yunus, Mohd Nizam; Kamis, Yamin (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2010)
Scholarly publishing is an industry which concerns about academic materials. From this research, this research aimed to show that scholarly industry is not only for the person that has basic writing skill but also for academicians. This study is about the publications of Shaharom TM Sulaiman, a lecturer from the Faculty of Information Management, UiTM Malaysia. It is important to document the publications of academicians from UiTM for the purpose of knowledge repository, and to capture the bibliographic information of each publication. This study could be used as a guideline to further enhance the scope to academicians from other faculties as well.